Improvement of gut-vascular barrier by terlipressin reduces bacterial translocation and remote organ injuries in gut-derived sepsis - Zenan Chang; Zenan Chang; Yinan Zhang; Ming Lin; Shihong Wen; Hanjin Lai; Yaqing Zhan; Xiufen Zhu; Zhikun Huang; Xuyu Zhang; Zimeng Liu (Frontiers Media S.A., 2022)
Gut-vascular barrier (GVB) serves as the last barrier to limit the migration of intestinal toxins into the blood circulation. The efficacy of terlipressin (a vasopressin V1 receptor agonist) in reducing GVB and multiple organ damage in gut-derived sepsis is unknown. In this study, we hypothesized that, besides other intestinal barriers, GVB play a key role in gut-derived sepsis and terlipressin improve GVB damage and then reduce bacterial translocation and organ injuries. In vivo, a cecal ligation and puncture mouse model was established. The mice were subjected to examine the damage of GVB determined by intestinal plasmalemma vesicle-associated protein-1(PV-1) and vascular endothelial-cadherin. And the intestinal permeability was assessed by translocation of intestinal bacteria and macromolecules. In vitro, transendothelial electrical resistance (TER) during interleukin (IL)-1β stimulation was measured on endothelial cells with or without small interfering RNA targeting β-catenin (si β-catenin). Terlipressin significantly improved GVB damage and reduced translocation of intestinal macromolecules and bacteria by activating PI3K signaling. Of note, intestinal PV-1 expression was significantly correlated with translocation of macromolecules, and dramatic increase of macromolecules was observed in intestinal tissues whereas fewer macromolecules and bacteria were observed in blood, liver and lung following terlipressin treatment. In vitro, terlipressin restored TER during IL-1β stimulation and si β-catenin transfection blocked the changes delivered by terlipressin. Collectively, terlipressin alleviated GVB damage and subsequent bacterial translocation via blood vessels after sepsis challenge, resulting in reduced distant organ injuries and the responsible mechanisms may involve the activation of PI3K/β-catenin pathway.